Optical absorption of Bi₁₂SiO₂₀:Sn crystals - Panchenko, T.V.; Diachenko, A.A. (Functional Materials, 2015)
The results of experimental research of stationary and photoinduced optical absorption of tin-doped Bi₁₂SiO₂₀:Sn crystals are presented. Peculiarities of the tin influence on the absorption are due to its occurrence into the crystal lattice in Sn⁴⁺ and Sn²⁺ charge states substituting for Si⁴⁺ ions.